2022
DOI: 10.1136/annrheumdis-2021-222029
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of disease flares by risk-adapted stratification of therapy withdrawal in juvenile idiopathic arthritis: results from the PREVENT-JIA trial

Abstract: ObjectivesTo investigate the ability of high-sensitivity C-reactive protein (hsCRP) and S100A12 to serve as predictive biomarkers of successful drug withdrawal in children with clinical remission of juvenile idiopathic arthritis (JIA).MethodsThis multicentre trial (PREVENT-JIA) enrolled 119 patients with JIA in clinical remission, and 100 patients reached the intervention phase in which the decision whether to continue or stop treatment was based on S100A12 and hsCRP levels. Patients were monitored for 12 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Our patients were on therapy for a small part of the time they were being followed up by specialists, and a large majority of those who transitioned to adult care had been weaned from treatment for over a year. This probably illustrates the pediatricians’ doubts about the future outcomes of these patients [ 16 ]. Adult/child studies on the evolutionary profile of these patients are necessary to assess the risk of recurrence in adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Our patients were on therapy for a small part of the time they were being followed up by specialists, and a large majority of those who transitioned to adult care had been weaned from treatment for over a year. This probably illustrates the pediatricians’ doubts about the future outcomes of these patients [ 16 ]. Adult/child studies on the evolutionary profile of these patients are necessary to assess the risk of recurrence in adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Well-designed trials that include serological or imaging biomarkers for absence of inflammation [ 25–27 ] are key to identify those patients with truly inactive disease vs those with subclinical inflammation not detectable by routine examination and tests, but likely to become apparent following a decrease or cessation of biologic therapy. The PREVENT-JIA trial, using pro-inflammatory protein biomarkers (S100A12 and high-sensitivity CRP) as a decision tool for stopping biologic therapy in patients in clinical remission, found fewer flares in those where biomarker levels were considered prior to stopping and longer time from stopping medication until first flare [ 28 ]. While CRP was available at start of biologic therapy in the current analysis, it was unavailable at the time of biologic stop and thus excluded from the Cox model.…”
Section: Discussionmentioning
confidence: 99%
“…However, Hinze et al [35] found that elevated S100A8/9 levels did not predict flare following TNFi withdrawal. Two studies found S100A12 to be a potentially useful predictive marker for stopping bDMARDs, although the correlation was moderate [35,36 ▪ ]. Antibodies to the nuclear oncoprotein DEK also show promise as a biomarker, with higher DEK autoantibody levels in patients who flared after TNFi discontinuation, although antibody levels at the time of discontinuation did not significantly differ between those who did and did not subsequently flare, limiting their current use as predictive biomarkers [37].…”
Section: Serologic Markers As Predictorsmentioning
confidence: 99%